Controlled isoflurane anesthesia exposure is required for reliable behavioral testing in murine surgical models - Kensuke Toyama; Joshua M. Spin; Yasunori Abe; Yasuyuki Suzuki; Alicia C. Deng; Markus U. Wagenhäuser; Takuya Yoshino; Joscha Mulorz; Shuang Liu; Philip S. Tsao; Masaki Mogi (Elsevier, 2019)
We investigated the effects of variations in anesthesia exposure time prior to conducting anxiety response behavioral testing in sham controls from an experimental murine model. The staying time in the center area of the Open Field test in the "long exposure" group was significantly decreased compared to that of the "short exposure" group. Significant correlation was found between anesthesia time and the duration of staying time in the center area. We conclude that anesthesia time may have a significant impact on behavioral anxiety testing in this context, and advise careful control of this parameter in protocol optimization in related surgical animal models. Keywords: Anesthesia, Anxiety response, Rodent model